The Implementation of Problem Based Learning with Reguku on the Topic of Immune System in High School - Kustiani, Eri; Widiyaningrum, Priyantini; Setiati, Ning (Journal of Biology Education, 2018)
This research aimed to find out the effectiveness of the implementation of problem-based learning with Reguku on the topic of immune system for high school to students’ attitude of health caring and learning outcomes for high school student. This research uses pre-experimental design approach which is helped with conducting one-group pretest-posttest design. There were four kinds of data analyzed in this research: (1) students’ score, (2) students’ attitude of health caring, (3) students’ response and (4) questionnaire of teacher’s response to problem-based learning with Reguku. Students’ learning outcomes was analyzed using N-gain formula and classical completeness test, meanwhile the students’ attitude of health caring, students’ and teacher’s response to problem-based learning with Reguku were analyzed descriptively using percentage. The students’ attitude of health caring indicated a good condition which was 76,02%. The data of learning outcomes for student were obtained from the score of posttest, daily activity, discussion sheet, and exercise. Collectively, 83,6% of the students from both classes passed the minimum passing score of classical completeness test and the increase of N-gain score is in medium criteria (0,345). Both the teachers and the students gave positive response on the implementation of problem-based learning with Reguku. Based on the research findings and discussion, it can be said that problem-based learning with Reguku is effective to be applied on the topic of immune system in SMA N 2 Bae Kudus.